Enhancing the estate administration through mediation in the estate distribution division - Drs Nasrul, Muhammad Amrullah; Mohd Alam Shah, Nurin Athirah; Halim, Akmal Hidayah (International Islamic University Malaysia, 2024)
PURPOSE: This paper explores the integration of mediation into the said agency as a strategic tool to streamline estate administration and resolve conflicts.METHODS:Applying a comprehensive library-based research methodology, this study reviews existing literature, legal frameworks, and case studies to evaluate the impact of mediation on estate administration through a proposed practice of mediation.RESULTS: Findings suggest that mediation offers a viable alternative to traditional litigation, providing a more amicable, cost-effective, and timely resolution to conflicts. The study highlights successful implementations of mediation in comparable jurisdictions, underscoring its potential benefits in reducing court caseloads and fostering harmonious settlements. Additionally, the paper proposes the creation of a mediation process flowchart to guide estate administrators and legal professionals in effectively implementing mediation.CONCLUSION: By integrating mediation into the estate administration process, the Estate Distribution Division can enhance its operational efficiency, ensuring fair and expeditious distribution of assets. The proposed flowchart is expected to give a clear formulation of the mediation process, ultimately promoting a more effective estate administration system in Malaysia.